THE POTENTIAL OF SEVERAL FLUORIDE-BASED VARNISHES AS REMINERALIZATION AGENTS: MORPHOLOGICAL STUDIES, DENTIN SURFACE HARDNESS, AND CRYSTALLINITY TESTS - Soekanto, Sri Angky; Fadillah, Fadiza; Nuraisiya, Putri; Gultom, Ferry; Sarwono, Agoeng T (International Journal of Applied Pharmaceutics, 2018)
Objectives: This study was conducted to analyze the effects of several fluoride-based varnishes: Sodium diamine fluoride (SDF), nanosilver fluoride (NSF), and propolis fluoride (PPF). Fluoride-based varnish is proven to remineralize and arrest caries progression with minimal side effects. SDF, the gold standard for this study, compared to NSF and PPF to observe the dentin morphology, hardness, and crystallinity test. Methods: Dentin blocks were allocated and divided into control groups and treatment groups with SDF (38%), NSF (3.16%, 3.66%, and 4.16%), and PPF (3%, 6%, and 10%). The dentin discs were demineralized using a demineralization solution (pHÂ 4.4) for 96 h. Each dentin disc in the treatment group received a topical application of various fluoride-based varnishes and was then subjected to pH cycling for 8Â days. The surface morphology of dentin was observed by a scanning electron micrograph (SEM), dentin hardness was analyzed by a Vickers microhardness tester, and the crystal characteristics of dentin blocks were investigated by X-ray diffraction (XRD). Results: This study showed crystal fluorapatite on the dentin surface of SDF and NSF. There was an amorphous layer on the dentin surface of PPF (10%) detected when using SEM. The Vickers hardness number of dentin increased after the application of SDF, NSF, and PPF. XRD revealed precipitates of apatite compounds, calcium compounds, and metal compounds in the treatment groups in higher concentrations than in the control (demineralized) group. Conclusion: It was concluded that SDF, NSF, and PPF were effective for dentin remineralization. Hence, NSF and PPF fluoride-based varnishes are promising as anticariogenic agents.